New Mythicomyia Coquillett, 1893 (Diptera: Mythicomyiidae: Mythicomyiinae) from Peru - Sánchez, Pável; Evenhuis, Neal (Zootaxa, 2024)
This work presents the first record of the family Mythicomyiidae from Peru, based on the descriptions of five new species of Mythicomyia Coquillett, 1893: Mythicomyia huk sp. nov. from Amazonas, Mythicomyia iskay sp. nov. from Amazonas, Ancash, Cajamarca, La Libertad, Lambayeque, Loreto, Piura and San Martín, Mythicomyia kinsa sp. nov. from Arequipa, Mythicomyia tawa sp. nov. from Arequipa, Ica and Moquegua, and Mythicomyia pisqa sp. nov. from Arequipa and Tacna. Illustrations of the new species, an updated key to South American fauna of Mythicomyia and a distribution map for the Peruvian species are also presented. It is worth noting that this work discusses the difficulty of confidently assigning the new species described herein to either of the two currently known subgenera of Mythicomyia, highlighting the need for a comprehensive revision of their limits. Until further study can be conducted to ascertain the status of each subgenus, all species are treated as Mythicomyia (s. lat.) without subgeneric attribution.